Editorial on the Special Issue “Advances in Cellulose-Based Hydrogels” - Lorenzo Bonetti; Christian Demitri; Laura Riva (Gels, 2022)
Cellulose is one of the most ubiquitous and naturally abundant biopolymers found on Earth and is primarily obtained from plants and other biomass sources [...]